Understanding Healthcare Information. - Robinson, Lyn (Facet Publishing, 2013)
Analyses the domain of healthcare information, its organizational structures and history, and the nature of its resources and the drivers for change affecting them. This title looks at examples of healthcare information resources from the perspective of different user groups, including healthcare professionals and consumers.